1996
DOI: 10.1029/96ja02664
|View full text |Cite
|
Sign up to set email alerts
|

Lower ionospheric cyclotron maser theory: A possible source of 2ƒce and 3ƒce auroral radio emissions

Abstract: A lower ionospheric electron cyclotron maser has recently been suggested as a possible source of natural radio emissions that have been observed with ground‐based instruments in the auroral zone. According to this theory, the observed emissions are interpreted as X mode electromagnetic waves at 2 and/or 3 times the ionospheric electron cyclotron frequency (ƒce). In the present study we carry out a more thorough analysis of the cyclotron maser instability, using a more complete growth rate expression and more r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 26 publications
0
58
0
Order By: Relevance
“…For example, several researchers have suggested that auroral roar may be generated in the X-mode by the cyclotron maser mechanism operating at F-region altitudes [Weatherwax et al, 1995;Yoon et al, 1996]. This mechanism predicts that auroral roar should be right elliptically polarized.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several researchers have suggested that auroral roar may be generated in the X-mode by the cyclotron maser mechanism operating at F-region altitudes [Weatherwax et al, 1995;Yoon et al, 1996]. This mechanism predicts that auroral roar should be right elliptically polarized.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Menietti et al [2016] surveyed possible regions of 5 kHz Z mode narrowband emissions in the lower density region of Saturn's magnetosphere and identified 6 possible source regions, one of which had relatively complete electron pitch angle coverage by the electron spectrometer onboard Cassini. Wave growth calculations based on the electron phase space distribution and cold plasma magnetoionic theory [Yoon et al, 1996 and1998] indicated that an unstable electron population with a temperature anisotropy and a weak loss cone might be the source for the 5 kHz Z mode narrowband emissions.…”
Section: Narrowband Emissionmentioning
confidence: 99%
“…In this section we treat these emissions using an analytical approach based on the work of Yoon et al (1996Yoon et al ( , 1998.…”
Section: Growth Rate Calculationsmentioning
confidence: 99%
“…In order to facilitate the analytical calculation of the growth rate of Z-mode and O-mode, we introduce a functional form for the distribution function similar to that of Yoon et al (1996) …”
Section: Growth Rate Calculationsmentioning
confidence: 99%
See 1 more Smart Citation